Moral decision-making during the COVID-19 pandemic: Associations with age, negative affect, and negative memory - Daley, Ryan T.; Cunningham, Tony J.; Kensinger, Elizabeth A. (Frontiers in Psychology, 2022)
The COVID-19 pandemic provided the opportunity to determine whether age-related differences in utilitarian moral decision-making during sacrificial moral dilemmas extend to non-sacrificial dilemmas in real-world settings. As affect and emotional memory are associated with moral and prosocial behaviors, we also sought to understand how these were associated with moral behaviors during the 2020 spring phase of the COVID-19 pandemic in the United States. Older age, higher negative affect, and greater reports of reflecting on negative aspects of the pandemic were associated with higher reported purchase of hard-to-find goods, while older age and higher negative affect alone were associated with higher reported purchase of hard-to-find medical supplies. Older age was associated with what appeared at first to be non-utilitarian moral behaviors with regard to the purchasing of these supplies; However, they also reported distributing these goods to family members rather than engaging in hoarding behaviors. These findings suggest that advancing age may be associated with engagement in utilitarian moral decision-making in real-world settings more than the sacrificial moral decision-making literature would suggest.